Prognostic and clinicopathological value of prognostic nutritional index in patients with multiple myeloma: a meta-analysis - Nie, Yanchen; Zhang, Zongxin; Tang, Xiaohuan (Frontiers in Oncology, 2025)
BackgroundPrognostic nutritional index (PNI) has been extensively investigated for its effect on forecasting multiple myeloma (MM) survival; however, the conclusions are conflicting. This meta-analysis identified an accurate MM prognosis forecasting role for the PNI.MethodsWe systematically searched PubMed, Web of Science, Embase, Cochrane Library, and CNKI databases until July 2, 2025, and evaluated the overall survival (OS) and progression-free survival (PFS) forecasting ability of the PNI by determining pooled hazard ratios (HRs) with 95% confidence intervals (CIs).ResultsThis study included seven articles involving 1120 participants. From the pooled findings, a lower PNI exhibited a remarkable correlation with unfavorable OS (HR = 2.62, 95% CI = 1.76–3.89) and shorter PFS (HR = 1.52, 95% CI = 1.23–1.89, p<0.001) of MM. Additionally, lower PNI was significantly associated with ISS stage III (odds ratio [OR]=1.80, 95% CI = 1.19–2.73, p=0.005). However, PNI did not have a marked correlation with sex (OR = 1.02, 95% CI = 0.71–1.47, p=0.900), age (OR = 1.1, 95% CI = 0.70–1.93, p=0.558), and lactate dehydrogenase (OR = 0.98, 95% CI = 0.57–1.69, p=0.955) in MM. The meta-analysis had some limitations, such as retrospective design, small sample size, and inconsistent cut-off values of PNI.ConclusionCollectively, the present work including 1120 patients showed the relationship between a lower PNI and unfavorable MM OS and PFS. Furthermore, a lower PNI was significantly associated with an advanced ISS stage of MM. The PNI can be a creditable and cost-effective factor for forecasting MM prognosis.